Comparing the efficacy of different methods of faecal microbiota transplantation via oral capsule, oesophagogastroduodenoscopy, colonoscopy, or gastric tube. (January 2023) - Lee, E.H.; Lee, S.K.; Cheon, J.H.; Koh, H.; Lee, J.A.; Kim, C.H.; Kim, J.N.; Lee, K.H.; Lee, S.J.; Kim, J.H.; Ahn, J.Y.; Jeong, S.J.; et al.
Summary: Background: The increasing prevalence of multidrug-resistant organism (MDRO) carriage poses major challenges to medicine as healthcare costs increase. Recently, faecal microbiota transplantation (FMT) has been discussed as a novel and effective method for decolonizing MDRO. Aim: To compare the efficacy of different FMT methods to optimize the success rate of decolonization in patients with MDRO carriage. Methods: This prospective cohort study enrolled patients with MDRO carriages from 2018 to 2021. Patients underwent FMT via one of the following methods: oral capsule, oesophagogastroduodenoscopy (EGD), colonoscopy, or gastric tube. Findings: A total of 57 patients underwent FMT for MDRO decolonization. The colonoscopy group required the shortest time for decolonization, whereas the EGD group required the longest (24.9 vs 190.4 days, P  = 0.022). The decolonization rate in the oral capsule group was comparable to that in the EGD group (84.6% vs 85.7%, P  = 0.730). An important clinical factor associated with decolonization failure was antibiotic use after FMT (odds ratio = 6.810, P  = 0.008). All four groups showed reduced proportions of MDRO species in microbiome analysis after FMT. Conclusion: Compared to other conventional methods, the oral capsule is an effective FMT method for patients who can tolerate an oral diet. The discontinuation of antibiotics after FMT is a key factor in the success of decolonization.